A before–after study of multidisciplinary Out-of-Hours handover: combining management and frontline efforts to create sustainable improvement. (17th February 2017) - Pennell, Christopher; Flynn, Lorna; Boulton, Belinda; Hughes, Tracey; Walker, Graham; McCulloch, Peter
Abstract: Objective: The importance of implementation strategy in systems improvement is increasingly recognized and both 'bottom-up' and 'top-down' approaches have significant barriers. A trial of a combined approach involving frontline and managerial staff therefore seems merited. We attempted to improve handover using a Human Factors-based approach integrated with a combined 'top and bottom' implementation strategy. Design: A before–after study was conducted across 9 months. Setting: The study was set in a 236 bed district general hospital. Participants: Participants included any member of staff involved in Out of Hours handover. Intervention: Existing processes were analysed using Human Factors methods. Changes made were based on this analysis and developed via facilitation between management and frontline staff. These included creating a single multidisciplinary handover, changing the venue, standardizing the meeting structure, developing an standard operating procedure for identifying unwell patients for handover and creating a clinical coordinator role. Main outcome measures: Meeting attendance, duration, start time efficiency, the type of patients handed over and the transfer of important information were measured pre- and post-intervention. Results: We found improvement in handover start time ( P = 0.002, r = 0) and multidisciplinary participation ( P = 0.002, r = −0.534). Handover of unwell patients improved, but not significantly. Communication of plan ( P < 0.001, r = 0.14) and pending tasks ( P < 0.001, r = 0.30) improved, but diagnosis ( P = 0.233, r = −0.05), history ( P = 0.482, r = −0.03) and comorbidities ( P = 0.19, r = −0.05) did not. Conclusions: The changes produced greater multidisciplinary participation, a broader focus and improved communication of plans and tasks outstanding. The 'top and bottom' implementation approach appeared valuable. Management involvement was essential for significant changes, while frontline staff involvement facilitated the design of context-specific practical solutions with staff buy-in.